Synthesis of gypsogenin derivatives with capabilities to arrest cell cycle and induce apoptosis in human cancer cells. Issue 1 (24th January 2018) - Zhang, Haochao; Mu, Yanling; Wang, Fengling; Song, Leling; Sun, Jie; Liu, Yongjun; Sun, Jingyong
Abstract : Thirty-two gypsogenin derivatives were synthesized and screened for their cytotoxic activities. Their structures were established using IR, 1 H NMR, 13 C NMR, and LC-MS spectroscopic data. In MTT assays nearly all the compounds displayed good cytotoxicity in the low μM range for several human tumour cell lines (A549, LOVO, SKOV3 and HepG2). Low IC50 values were obtained especially for the carboxamides 7a –7j, for an oxime derivative 3 and a (2, 4-dinitrophenyl)hydrazono derivative 4 . In particular, the IC50 values of compounds 4 (IC50  = 2.97 ± 1.13 µΜ) and 7 g (IC50  = 3.59 ± 2.04 µΜ) against LOVO cells were found to be much lower than those of the other derivatives and parent compound. These compounds were submitted to an extensive biological testing and proved compounds 4 and 7 g to act mainly by an arrest of the tumour cells in the S phase of the cell cycle. In addition, compounds 4 and 7 g triggered the apoptotic pathway in cancer cells, showing high apoptosis ratios.